Effectiveness Of Activated Nipah Bark Charcoal In Reducing Free Fatty Acids And Peroxide Numbers In Waste-Cooked Oil - Naily Ulya; Fajar Hidayanto; Oto Prasadi; Fadhil Muhammad Nuryanto; Meta Aquarista Galia (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Used cooking oil contains high levels of free fatty acids (FFA) and peroxide compounds, posing health and environmental risks. This study explores the purification of used cooking oil using activated carbon derived from nipa palm (Nypa fruticans) peel, which is rich in lignocellulose (48.22% cellulose, 26.4% hemicellulose, 17.8% lignin). The peel underwent carbonization and chemical activation with NaOH 0.5 N. FTIR analysis confirmed the presence of functional groups –OH and C=O, indicating enhanced adsorption capability. A Completely Randomized Design (CRD) was applied with adsorption times of 30, 60, and 90 minutes, repeated five times. Parameters measured included FFA, peroxide value, water content, viscosity, and pH. Results showed significant improvements: FFA reduced from 1.60% to 0.29%, peroxide value from 7.10 to 3.76 meq/kg, water content from 0.60% to 0.26%, and viscosity from 64.48 to 56.78 MPas, while pH increased from 6.06 to 6.62. These findings demonstrate that activated carbon from nipa peel effectively adsorbs polar and oxidative compounds, improving oil quality. The process supports circular economy principles by converting agricultural waste into valuable adsorbents, offering a low-cost and eco-friendly solution for oil purification.